2022
DOI: 10.1088/1748-605x/ac489e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passage number of genetically modified TGF-β3 expressing primary chondrocytes on the chondrogenesis of ATDC5 cells in a 3D coculture system

Abstract: Due to the lack of blood vessels, nerves and lymphatics, articular cartilage is difficult to repair once damaged. Tissue engineering is considered to be a potential strategy for cartilage regeneration. Successful tissue engineering strategies depend on the effective combination of biomaterials, seed cells and biological factors. In our previous study, a genetically modified coculture system with chondrocytes and ATDC5 cells in an alginate hydrogel has exhibited a superior ability to enhance chondrogenesis. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Chen et al found that late passage of chondrocytes (P5) can express TGF-β3 at a high level upon viral vector transfection. ADTC5 cells (mouse teratocarcinomaorigin chondrogenic cells) were effectively promoted to chondrogenic differentiation upon coculture with those genetically modified chondrocytes [7]. Xue et al applied high-throughput RNA sequencing to study the influence of micro-cavity alginate hydrogel on human cartilage chondrocytes [8].…”
mentioning
confidence: 99%
“…Chen et al found that late passage of chondrocytes (P5) can express TGF-β3 at a high level upon viral vector transfection. ADTC5 cells (mouse teratocarcinomaorigin chondrogenic cells) were effectively promoted to chondrogenic differentiation upon coculture with those genetically modified chondrocytes [7]. Xue et al applied high-throughput RNA sequencing to study the influence of micro-cavity alginate hydrogel on human cartilage chondrocytes [8].…”
mentioning
confidence: 99%